2021
DOI: 10.1002/adsu.202000285
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Different MOF and Non‐MOF Porous Materials for SO2 Adsorption and Separation Showing the Importance of Small Pore Diameters for Low‐Pressure Uptake

Abstract: The search for adsorbents for flue gas desulfurization processes is a current interest. For the first time, a comparative experimental study of SO2 adsorption by porous materials including the prototypical metal–organic frameworks NH2‐MIL‐101(Cr), Basolite F300 (Fe‐1,3,5‐BTC), HKUST‐1 (Cu‐BTC), the zeolitic imidazolate frameworks (ZIF)‐8, ZIF‐67, the alumosilicate Zeolite Y, the silicoaluminumphosphate (SAPO)‐34, Silica gel 60, the covalent triazine framework (CTF)‐1, and the active carbon Ketjenblack is carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 93 publications
(87 reference statements)
5
46
0
2
Order By: Relevance
“…On the other hand, the nanomaterials generally and metal-organic frameworks in nano-size-scale (MOF-NPs) especially have many advantages and auspicious properties like chemical and thermal stability, porosity, large surface area, highly magnetic, excellent adsorbent materials …., etc. [23][24][25][26][27][28][29][30][31][32]. Different excellent physicochemical properties of the MOF-NPs make these nanomaterials are very sensitive and selective tools for bonding to biological and organic molecules and can be simply interacted moreeffective than bulk state materials [33].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the nanomaterials generally and metal-organic frameworks in nano-size-scale (MOF-NPs) especially have many advantages and auspicious properties like chemical and thermal stability, porosity, large surface area, highly magnetic, excellent adsorbent materials …., etc. [23][24][25][26][27][28][29][30][31][32]. Different excellent physicochemical properties of the MOF-NPs make these nanomaterials are very sensitive and selective tools for bonding to biological and organic molecules and can be simply interacted moreeffective than bulk state materials [33].…”
Section: Introductionmentioning
confidence: 99%
“…This confirms earlier results by Martínez-Ahumada et al that MIL-101(Cr) gradually loses its crystallinity and surface area after dry SO 2 sorption at 298 K. [28] Similarly, we found in a recent study that NH 2 -MIL-101(Cr) lost porosity after dry and especially after humid SO 2 exposure (Figure S14b, SI). [68] The instability of MIL-101(Cr) towards SO 2 was explained by its comparatively hydrophilic nature. [28] We suggest that both MIL-101(Cr) and NH 2 -MIL-101(Cr) are unstable because the SO 2 can interact with the chromium-aqua and -hydroxido ligand (CrÀ OH 2 and CrÀ OH) in the trinuclear secondary building unit (SBU) (Figure S1a Mounfield et al have confirmed the formation of bisulfite species and, together with theoretical simulations, suggested that the degradation of the MIL-125 framework proceeds by reaction with water and the dissociation of water or sulfurous acid.…”
Section: Resultsmentioning
confidence: 99%
“…[31,32] In addition, it has been recently pointed out that small micropore diameters in the range of approximately 4to 8 could be advantageous for low-pressure SO 2 uptake. [33] MOFs with methyl-functionalized linkers could be agood candidate for tailoring micropore diameters to the optimal range and at the same time having moderate non-covalent van der Waals (vdW) interactions with SO 2 molecules for sufficient SO 2 affinity but still facile (desorption) regeneration. Methyl-functionalized MOFs have been shown to display enhanced CO 2 uptake affinity, [34,35] but were not explored for SO 2 sorption and separation to the best of our knowledge.W epropose that MOFs with an already feasible topology could be tuned in their pore diameter for an efficient SO 2 separation through methyl-functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…The other one is polar amino groups in the framework as sites for hydrogen‐bonding interactions with SO 2 [31, 32] . In addition, it has been recently pointed out that small micropore diameters in the range of approximately 4 to 8 Å could be advantageous for low‐pressure SO 2 uptake [33] …”
Section: Introductionmentioning
confidence: 99%